Влияния параметров исходных заготовок для производства железнодорожных колёс на процесс горячей пластической деформации - Бабаченко, А. И.; Дёмина, Е. Г.; Кныш, А. В.; Головко, А. Н.; Ашкелянец, Антон Владимирович (ТОВ "Укрметалургінформ "НТА", 2016)
Впервые показано влияние геометрических параметров исходной заготовки на распределение степени накопленной деформации и положение осевой некачественной зоны их макроструктуры в колёсных заготовках после горячей пластической деформации. Установлено, что при факторе формы колёсных заготовок (H / D), равном 0,73, 0,84 и 1,11, степень накопленной деформации в ободе колёс изменяется незначительно и составляет порядка 85 %.

For the first time the effect of geometrical parameters of the incoming billet on the distribution of cumulative degree of deformation and location of the unsound core zone of its macrostructure in the wheel billets after the hot plastic deformation process has been shown. It has been established that when the form factor of wheel billets (H / D) equals to 0.73, 0.84 and 1.11 the degree of cumulative deformation of wheel rims changes slightly and is about 85 %.
The influence of parameters of an incoming billet for the manufacturing of railway wheels on the hot plastic deformation process
Keywords: колёсная заготовка; фактор формы; компьютерное моделирование; горячая пластическая деформация; макроструктура; wheel billet; form factor; computer simulation technique; hot plastic deformation; macrostructure